2021
DOI: 10.1007/s10750-021-04721-8
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plant mats promoted the decomposition of native leaf litter by micro-, meio-, and macroinvertebrates in an eutrophic freshwater lake in the Three Gorges Reservoir area, China

Abstract: To investigate the effect of invasive Alternanthera philoxeroides mats on native leaf litter decomposition, we allocated two native leaf species of contrasting recalcitrance (Neosinocalamus affinis and Ficus virens) in litterbags with four different mesh sizes (0.025, 0.042, 0.5, and 5 mm) and the bags were either incubated under floating A. philoxeroides mats (Vegetated site) or under floating plastic foam boards without A. philoxeroides mats (Unvegetated site) for 65 days in Jianhu Lake, China, in July 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(67 reference statements)
1
4
0
Order By: Relevance
“…In coarse mesh bags, decomposition is the result of three main processes such as microbial breakdown, macroinvertebrate consumption, and physical abrasion, in which microbial breakdown accounts for the majority of decomposition in fine mesh bags (Fugère et al, 2020;Bärlocher et al, 2020). Decomposition rates increased as the size increased in litterbags (Chen et al, 2022b). This was similar to the case when comparing coarse to fine mesh litter bags; decomposition rates were higher in coarse mesh litter bags in our experiment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In coarse mesh bags, decomposition is the result of three main processes such as microbial breakdown, macroinvertebrate consumption, and physical abrasion, in which microbial breakdown accounts for the majority of decomposition in fine mesh bags (Fugère et al, 2020;Bärlocher et al, 2020). Decomposition rates increased as the size increased in litterbags (Chen et al, 2022b). This was similar to the case when comparing coarse to fine mesh litter bags; decomposition rates were higher in coarse mesh litter bags in our experiment.…”
Section: Discussionsupporting
confidence: 86%
“…Because the litter decomposition process depends directly and indirectly on many environmental, biological, and anthropogenic factors, it can be used as an indicator of soil health (Fugère et al, 2020;Bärlocher et al, 2020;Wang et al 2020a,b). Organisms such as microbes and soil invertebrates lead to decomposition, so population variations will change this process (Chen et al, 2022b). In coarse mesh bags, decomposition is the result of three main processes such as microbial breakdown, macroinvertebrate consumption, and physical abrasion, in which microbial breakdown accounts for the majority of decomposition in fine mesh bags (Fugère et al, 2020;Bärlocher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, eutrophication caused an increase in plant SOD activity and a reduction of plant phenolics and starch contents in both native species, which reduced the ability of native species to resist invasion. Previous studies have shown that plant-invaded habitats have increased water turbidity and nitrogen and organic matter concentrations, which is associated with the ability of invaders to modify habitats and increase eutrophication. , Moreover, invasive plant-habitat interactions, resulting in reduced habitat heterogeneity, may have a negative impact on plant community dynamics, which may then promote continued invasion. ,, Therefore, eutrophication in the littoral zone has a suppressive effect on the morphology and physiology of native plants, causing habitat degradation, which may be followed by continued plant invasion, i.e., a vicious cycle that exacerbates the degradation of littoral habitats.…”
Section: Discussionmentioning
confidence: 99%
“…12,92 Moreover, invasive plant-habitat interactions, resulting in reduced habitat heterogeneity, may have a negative impact on plant community dynamics, which may then promote continued invasion. 90,93,94 Therefore, eutrophication in the littoral zone has a suppressive effect on the morphology and physiology of native plants, causing habitat degradation, which may be followed by continued plant invasion, i.e., a vicious cycle that exacerbates the degradation of littoral habitats.…”
Section: Discussionmentioning
confidence: 99%